2015
DOI: 10.4141/cjas-2014-183
|View full text |Cite
|
Sign up to set email alerts
|

Effect of sodium butyrate on intestinal inflammatory response to lipopolysaccharide in broiler chickens

Abstract: G. 2015. Effect of sodium butyrate on intestinal inflammatory response to lipopolysaccharide in broiler chickens. Can. J. Anim. Sci. 95: 389Á395. The aim of this study was to investigate the effect of sodium butyrate (SB) supplementation on intestinal inflammatory response to lipopolysaccharide (LPS) in broiler chickens. A total of 120 one-day-old chickens (Arbor Acres) were divided into two groups and fed a control diet (without SB) or 1.00 g SB kg(1 diet. Half of the chickens fed each diet were injected intr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 41 publications
1
18
0
Order By: Relevance
“…Immune stress is often associated with the inflammation response, and cytokines released in the inflammation response could promote metabolism and suppress anabolism of carbohydrate, protein and fat to inhibit growth of animals ( Klasing, 1988 , Johnson, 1997 , Webel et al., 1997 , Sijben et al., 2001 , Hwang et al., 2008 ). Pro-inflammatory cytokines such as IL-1β, IL-6 and tumor necrosis factor-α (TNF-α) originated from macrophages were the major cellular messengers initiating metabolic cascade alterations following the innate immune response ( Jiang et al., 2015 ). Lipopolysaccharide was demonstrated to increase pro-inflammatory cytokines secretion and suppress animal growth ( Takahashi, 2012 , Tan et al., 2014 , Li et al., 2015b ).…”
Section: Discussionmentioning
confidence: 99%
“…Immune stress is often associated with the inflammation response, and cytokines released in the inflammation response could promote metabolism and suppress anabolism of carbohydrate, protein and fat to inhibit growth of animals ( Klasing, 1988 , Johnson, 1997 , Webel et al., 1997 , Sijben et al., 2001 , Hwang et al., 2008 ). Pro-inflammatory cytokines such as IL-1β, IL-6 and tumor necrosis factor-α (TNF-α) originated from macrophages were the major cellular messengers initiating metabolic cascade alterations following the innate immune response ( Jiang et al., 2015 ). Lipopolysaccharide was demonstrated to increase pro-inflammatory cytokines secretion and suppress animal growth ( Takahashi, 2012 , Tan et al., 2014 , Li et al., 2015b ).…”
Section: Discussionmentioning
confidence: 99%
“…The potential to influence a wide array of cellular functions such as inhibition of inflammation and carcinogenesis, reinforcement of various components of the colonic defence barrier and reduction of oxidative stress have been reported in humans [18, 19]. Likewise, dietary butyrate improves the intestinal morphology and function of chicken and partially attenuates inflammatory responses caused by liposaccharide [20]. Potential benefits of butyrate have also been proved in pigs, and the reduction in diarrhoea incidence by the addition of butyrate has been attributed to the improvement of intestinal integrity [21].…”
Section: Introductionmentioning
confidence: 99%
“…It had been used to imitate microbial stress in broilers (Korver and Klasing 1997). Previous studies in broilers revealed that LPS challenge compromised growth performance (Korver and Klasing 1997;Li et al 2015), impaired both innate and adaptive immunity (Korver and Klasing 1997), and induced intestinal inflammation coupled with a damage of intestinal structure and barrier function as evidenced by the destructive intestinal morphology and tight junctions (Hu et al 2011;Jiang et al 2015;Li et al 2015). Yeast oligosaccharide had been shown to improve performance (Morales-Lopez and Brufau 2013) and to modulate systemic and intestinal immune responses in LPS-challenged broilers (Morales-Lopez and Brufau 2013; Shanmugasundaram et al 2014).…”
Section: Introductionmentioning
confidence: 99%